EXOGENIC AND NEOTECTONIC PROCESSES IN THE WEST SPITSBERGEN UNDERWATER MARGIN DURING THE LATE CENOZOIC - Zakharenko V.S.; Tarasov G.A.; Matishov G.G.; Romanchenko A.Y. (My University, 2007)
The purpose of this study is to define basic faults in the bottom topography of the West Spitsbergen underwater margin and estimate proportions between exogenic and endogenic processes in this region during the Quaternary. This work is based on the following materials of the Marine Arctic Geological Expedition: seismoacoustic time sections, a map of local topography, a map of tectonic deformations based on CMP data, a map of basement structural zoning, a neotectonic map, and a state geological map.
Keywords: WEST SPITSBERGEN; UNDERWATER MARGIN; LATE CENOZOIC; EXOGENIC AND NEOTECTONIC PROCESSES; Cenozoic::Quaternary; Кайнозой::Четвертичная